Diastereoselective Synthesis of trans‐2, 3‐Diaryl(heteroaryl)‐3, 6‐dihydropyrans by an Allylboration/Ring‐Closing‐Metathesis Sequence. Issue 23 (21st June 2017) - Nocquet, Pierre‐Antoine; Corbu, Andrei; Meerpoel, Lieven; Stansfield, Ian; Berthelot, Didier; Angibaud, Patrick; Cossy, Janine
Abstract : trans ‐2, 3‐Diaryl(heteroaryl)‐dihydropyrans were synthesized by an allylboration/ring‐closing‐metathesis sequence, using allylboranes formed in situ from the corresponding allylic alcohols. Aryl(heteroaryl) substituents were thus installed diastereoselectively onto dihydropyran rings in a trans fashion. These disubstituted dihydropyrans were further transformed into monosaccharide‐like tetrahydropyrans. Abstract : As diarylated glycals and pseudoglycals are considered good starting backbones for potential kinase inhibitors, the synthesis of new precursors such as 2, 3‐diaryl(heteroaryl)‐dihydropyrans is important. Such compounds were synthesized starting from aryl(heteroaryl)ated alcohols and aryl(heteroaryl)ated aldehydes by using an allylboration/ring‐closing‐metathesis sequence.